An introduction to digital signal processing - Karl, John H. (Academic Press, 1989)
An Introduction to Digital Signal Processing is written for those who need to understand and use digital signal processing and yet do not wish to wade through a multi-semester course sequence. Using only calculus-level mathematics, this book progresses rapidly through the fundamentals to advanced topics such as iterative least squares design of IIR filters, inverse filters, power spectral estimation, and multidimensional applications--all in one concise volume. This book emphasizes both the fundamental principles and their modern computer implementation. It presents and demonstrates how simple the actual computer code is for advanced modern algorithms used in DSP. Results of these programs, which the reader can readily duplicate and use on a PC, are presented in many actual computer drawn plots. Key Features * assumes no previous knowledge of signal processing but leads up to very advanced techniques combines exposition of fundamental principles with practical applications * includes problems with each chapter * presents in detail the appropriate computer algorithums for solving problems.